Correlation of Mean Corpuscular Hemoglobin, Mean Corpuscular Hemoglobin Concentration and Platelet to Hemoglobin Ratio with the Degree of Dengue Virus Infection in Pediatric Patients - Alim, Fika Nurul; Jatmiko, Safari Wahyu; Puspitasari, Metana (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study aimed to evaluate the correlation between MCH, MCHC, and PHR with the severity of DVI in pediatric patients. Methodology: A cross-sectional observational study was conducted on 47 pediatric DVI patients at PKU Muhammadiyah Sampangan Hospital, Surakarta. Medical records from January to May 2024 were analyzed. Data were statistically evaluated using Spearman’s test to determine the correlation between variables. Results: Among 47 patients, 57.45% had dengue without warning signs, while 42.55% had dengue with warning signs, with no cases of severe dengue. There was no significant correlation between MCH (p=0.383, r=0.130), MCHC (p=0.457, r=-0.111), or PHR (p=0.064, r=-0.273) and the severity of DVI. Applications/Originality/Value: This study examines the roles of MCH, MCHC, and PHR in pediatric dengue virus infection, finding no significant correlation with disease severity. It provides a basis for future research on alternative hematological markers to enhance clinical assessment. This research introduces PHR as a novel parameter in dengue studies, providing a unique perspective on its potential relevance to disease pathophysiology.